Intralingual translation and translanguaging: fostering metacognition in foreign language teaching for trainee translators and interpreters - Seel, Olaf Immanuel (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2026)
The translation-related learning and teaching of foreign languages in translation/interpreting studies attaches particular importance to learner-centredness. Two important components of lerner-centredness are the learner autonomy and the metacognition that is essential for its fostering. The aim of this article is to show the extent to which intralingual translation and translanguaging are helpful tools for promoting the metacognition of prospective translators, to point out the possible areas of application and the foreign language and translational skills they promote, and to demonstrate the importance of promoting metacognition in translation-related foreign language teaching.